Do rural migrants benefit from labor market agglomeration economies? Evidence from Chinese cities. (27th July 2020) - Yang, Guangliang; Li, Lixing; Fu, Shihe
Abstract: We combine the 2005 China Inter‐Census Population Survey data and the 2004 China Manufacturing Census to test whether workers, particularly rural migrants, benefit from labor market Marshallian externalities. We find that workers in general, and rural migrants in particular, benefit from labor market pooling effects (measured by total employment in a city‐industry cell) and human capital externalities (measured by share of workers with a college degree or above in a city‐industry cell). These findings are robust to various sorting bias tests. However, rural migrants benefit much less than do local or urban workers, possibly because rural migrants lack social networks and are discriminated doubly in terms of being both "rural" and "migrants." Our findings have policy implications on how Chinese cities can become skilled during the rapid urbanization process coupled with global competition.